Characterization of the secondary metabolite biosynthetic gene clusters in archaea. (February 2019) - Wang, Shengqin; Zheng, Zhihong; Zou, Huixi; Li, Nan; Wu, Mingjiang
Abstract: Secondary metabolites are a range of bioactive compounds yielded by bacteria, fungi and plants, etc. The published archaea genomic data provide the opportunity for efficient identification of secondary metabolite biosynthetic gene clusters (BGCs) by genome mining. However, the study of secondary metabolites in archaea is still rare. By using the antiSMASH, we found two main putative secondary metabolite BGCs, bacteriocin and terpene in 203 Archaea genomes. Compared with the genomes of Euryarchaeota that usually lives in less complexity of environment, the genomes of Crenarchaeota usually contained more abundant bacteriocin. In these archaea genomes, we also found the positive correlation between the abundance of bacteriocin and the abundance of CRISPR spacer, suggesting the bacteriocin might be a crucial component of the innate immune system that defense the microbe living in the common environment. The structure analysis of the bacteriocin gene clusters gave a clue that the assisted genes located at the edge of clusters evolved faster than the core biosynthetic genes. To the best of our knowledge, we are the first to systematically explore the distribution of secondary metabolites in archaea, and the investigation of the relationship between BGC and CRISPR spacer expands our understanding of the evolutionary dynamic of these functional molecules.